1998
DOI: 10.1161/01.cir.98.22.2390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Patterns on Measures of Lipid Peroxidation

Abstract: Background-Free radical-mediated oxidative damage to lipids is thought to be an important process in the pathogenesis of atherosclerosis. Although previous studies have demonstrated a beneficial impact of antioxidant vitamin supplements on lipid peroxidation, the effect of dietary patterns on lipid peroxidation is unknown. Methods and Results-During the 3-week run-in period of a randomized trial, 123 healthy individuals were fed a control diet, low in fruits, vegetables, and dairy products, with 37% of calorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
2
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(77 citation statements)
references
References 38 publications
2
66
2
7
Order By: Relevance
“…In addition, blood pressure reductions began in the second week of intervention and continued for the 6-week duration of the study, reaching targets observed after drug therapy (34). A substudy using the DASH diet demonstrated that this modification in diet resulted in an increase in serum antioxidant capacity and a decrease in malondialdehyde, an in vitro marker of lipid peroxidation, suggestive of a reduction in oxidative stress (35). The DASH 2 study has further highlighted the benefit of following the combination DASH diet as well as reducing sodium intake.…”
Section: Antioxidants and Their Effects On Oxidative Stress In Hypertmentioning
confidence: 92%
“…In addition, blood pressure reductions began in the second week of intervention and continued for the 6-week duration of the study, reaching targets observed after drug therapy (34). A substudy using the DASH diet demonstrated that this modification in diet resulted in an increase in serum antioxidant capacity and a decrease in malondialdehyde, an in vitro marker of lipid peroxidation, suggestive of a reduction in oxidative stress (35). The DASH 2 study has further highlighted the benefit of following the combination DASH diet as well as reducing sodium intake.…”
Section: Antioxidants and Their Effects On Oxidative Stress In Hypertmentioning
confidence: 92%
“…Toutefois, la plupart des études in vivo [14,18,23,24,29,30,33,53] montrent que la consommation en fruits et légumes chez des sujets en bonne santé n'entraîne pas de façon significative une diminution des dommages oxydatifs au niveau des lipides ou de l'ADN. Ces résultats sont évidemment décevants puisque cela est en contradiction avec le fait que la concentration plasmatique en antioxydants est augmentée après un apport interventionnel en fruits et légumes.…”
Section: Influence De La Consommation De Fruits Et Légumes Sur Les Maunclassified
“…However, the beneficial effects of this level of consumption have not been examined. Studies to date have concentrated on dietary enhancement of volunteers with carotenoid-rich vegetables (Hininger et al, 1997;van het Hof et al, 1999;Bub et al, 2000;Chopra et al, 2000) or provided subjects with a highly controlled diet with a very high fruit and vegetable component (9-10 servings per day) (Cao et al, 1998;Miller et al, 1998). Previous studies attempting to increase fruit and vegetable consumption in free-living volunteers demonstrated increases in plasma antioxidants (Zino et al, 1997), but no significant increase in plasma antioxidant capacity (Record et al, 2001).…”
Section: Introductionmentioning
confidence: 99%